Situation Report: Hungary, 16 February 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Report on the Fulfillment of the 1970 Plan Hungarian Parliament Meets Youth Anniversary of the Hungarian Pioneers' Association Five-Years Hungarian-Yugoslav Trade Agreement Signed Hungary's Tourist Trade in 1970 Annual Accounting in the Farmers' Co-Operatives